Clinical and pathological analysis of primary well-differentiated neuroendocrine tumors in the kidney- a case series - Dan Yuan; Jing Wu; Dong-Yue Wang; Jin-Jing Wang (BMC Urology)
Abstract Objective To investigate the clinicopathological characteristics and key diagnostic/therapeutic features of primary well-differentiated neuroendocrine tumors (WDNET) of the kidney. Methods Retrospective analysis of 4 primary renal WDNET patients, including clinical features, pathological findings (Macroscopic and microscopic), immunophenotype, treatment, and outcomes. Results All 4 patients were female (mean age: 55 ± 7.83 years), One patient occasionally experienced mild low back pain, one presented with “palpitations and fatigue,” and the remaining two were incidentally found to have renal masses during abdominal ultrasound or CT examination.Macroscopic findings: Mean tumor diameter 6.1 ± 2.2 cm(range: 3.5–8.8 cm), solid gray-white/yellow cut surfaces. Microscopic findings: Characteristic trabecular/rosette-like patterns, uniform cells with “salt-and-pepper” chromatin, and rare mitotic activity. Immunohistochemistry(IHC): Positive for Synaptophysin (Syn), Chromogranin A(CgA), CD56, and Cytokeratin (CK); negative for renal markers; low Ki67 index. Two patients underwent radical nephrectomy, and two had partial nephrectomy. During follow-up (1–77 months), one patient developed liver metastasis at 50 months post-operation (stabilized with PRRT), while others showed no recurrence. Conclusion Primary renal WDNET is clinically rare and lack specific manifestations, often misdiagnosed as renal cell carcinomas. Definitive diagnosis requires characteristic histomorphology combined with immunohistochemical markers. Currently, there is no unified grading system, and surgical resection remains the main treatment approach. However, prognostic factors and treatment responses remain unclear, necessitating further studies with larger case cohorts for comprehensive investigation.